Estimation of Rainwater Harvesting Potential in an Educational Institute of Faisalabad, Pakistan - Husnain, Syed Ali; Tariq, Khawaja Adeel; Khan, Nouman (Journal of Sustainability Perspectives, 2022)
Pakistan is on verge of facing severe water scarcity issues by 2025. An exponential increase in population increases the water demand as most of the population in the country depends on groundwater. Over extraction of groundwater is causing depletion in the groundwater table at an alarming rate. Water conservation is becoming the need of time. Rainwater Harvesting is one the best methods that can be used to conserve water. This paper aims to determine the total volume of water that can be conserved from Rainfall on the Rooftop at the University of Faisalabad, Amin Campus located in an industrial city Faisalabad, Pakistan. For this purpose, water usage on the campus is estimated. The area of the campus rooftop is measured by conducting a topographic survey. Rainfall data from the year 1981-2021 is collected and average monthly rainfall is calculated. The soil Conservation Service Curve Number method is adopted to calculate the run-off. Results indicated that about 1300 cubic meters of water can be conserved per year which will cover about 20-25 percent of the total water demand of the campus if a Rainwater Harvesting System is installed at the campus.Keyword: Rainwater Harvesting, Water Conservation, Water Scarcity